A Mixed Method Study on the Cultural and Academic Correlates of Pre-Mathematical Skills among Early Grade Learners - Dash, Priya Ranjan (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
It is empirical from the research findings of last couple of decades that mathematics learning has a significant contribution to individuals‘ cognitive as well as intellectual abilities. Mathematics is one of the best means to inculcate the enrichment of different higher order thinking skills like critical thinking, creative thinking, and analytical thinking as well as reasoning skills. When we analyze the style and strength of mathematics learning of learners it is understood that Mathematisation of mind starts at the early childhood when learners start acquiring pre-mathematical skills. Pre-mathematical skills are the set of mathematical skills learned by early grade learners including pre-school learners. These skills include learning to count numbers, learning the proper sequencing of numbers, learning to determine which shapes are bigger or smaller, learning to count objects on a screen or book, the correct pronunciations of numbers. These also include the primary ideas on volume, measurement and concepts of more/ less etc. In the present study seventy early grade learners are studied. In the first half of this paper Pre-Mathematical Skill is quantitatively analyzed in relation to academic correlates like years in schooling process, medium of instruction, public or privately managed schools and cultural correlates like ethnicity as well as socio-economic experience of the learners. The second part deals with the analysis of qualitative information on Pre-Mathematical Skills followed by educational implication of the study.